Comprehensive analysis of MAPK gene family in upland cotton (Gossypium hirsutum) and functional characterization of GhMPK31 in regulating defense response to insect infestation - Fuqiu Wang; Sijia Liang; Guanying Wang; Qiongqiong Wang; Zhongping Xu; Bo Li; Chunyang Fu; Yibo Fan; Tianyu Hu; Muna Alariqi; Amjad Hussain; Jinglin Cao; et al. (Plant Cell Reports, 2024)
Key message The transcriptomic, phenotypic and metabolomic analysis of transgenic plants overexpressing GhMPK31 in upland cotton revealed the regulation of H 2 O 2 burst and the synthesis of defensive metabolites by GhMPK31 . Abstract Mitogen-activated protein kinases (MAPKs) are a crucial class of protein kinases, which play an essential role in various biological processes in plants. Upland cotton ( G. hirsutum ) is the most widely cultivated cotton species with high economic value. To gain a better understanding of the role of the MAPK gene family, we conducted a comprehensive analysis of the MAPK gene family in cotton. In this study, a total of 55 GhMPK genes were identified from the whole genome of G. hirsutum . Through an investigation of the expression patterns under diverse stress conditions, we discovered that the majority of GhMPK family members demonstrated robust responses to abiotic stress, pathogen stress and pest stress. Furthermore, the overexpression of GhMPK31 in cotton leaves led to a hypersensitive response (HR)-like cell death phenotype and impaired the defense capability of cotton against herbivorous insects. Transcriptome and metabolomics data analysis showed that overexpression of GhMPK31 enhanced the expression of H 2 O 2 -related genes and reduced the accumulation of defensive related metabolites. The direct evidence of GhMPK31 interacting with GhRBOHB (H 2 O 2 -generating protein) were found by Y2H, BiFC, and LCI. Therefore, we propose that the increase of H 2 O 2 content caused by overexpression of GhMPK31 resulted in HR-like cell death in cotton leaves while reducing the accumulation of defensive metabolites, ultimately leading to a decrease in the defense ability of cotton against herbivorous insects. This study provides valuable insights into the function of MAPK genes in plant resistance to herbivorous insects.